Rational therapeutic combinations with histone deacetylase inhibitors for the treatment of cancer - Thurn, K Ted (2011)
Histone deacetylases (HDACs) regulate the acetylation of a variety of histone and nonhistone proteins, controlling the transcription and regulation of genes involved in cell cycle control, proliferation, survival, DNA repair and differentiation. Unsurprisingly, HDAC expression is frequently altered in hematologic and solid tumor malignancies. Two HDAC inhibitors (vorinostat and romidepsin) have been approved by the US FDA for the treatment of cutaneous T-cell lymphoma. As single agents, treatment with HDAC inhibitors has demonstrated limited clinical benefit for patients with solid tumors, prompting the investigation of novel treatment combinations with other cancer therapeutics. In this article, the rationales and clinical progress of several combinations with HDAC inhibitors are presented, including DNA-damaging chemotherapeutic agents, radiotherapy, hormonal therapies, DNA methyltransferase inhibitors and various small-molecule inhibitors. The future application of HDAC inhibitors as a treatment for cancer is discussed, examining current hurdles to overcome before realizing the potential of this new approach.